BOTHA, Pieter Willem Inventory of documents - BOTHA, Pieter Willem (ARCA, 2017)
Private papers of P.W. Botha, National Party MP George [1948-1984], Deputy Minister Interior [1958-1961], Minister of Housing [1961-1964], Community Development [1961-1966], Coloured Affairs [1961-1966], Public Works [1964-1966], Defence [1966-1980], National Security [1978-1980], National Intelligence Service [1980], Prime Minister [1978-1983], State President [1984-1989]
COVERAGE 1911-1989; 2095 Files; 55,80 Metres. AUDIO CASSETTES IN ARCA COLLECTION = 35
Keywords: BOTHA, Pieter Willem; Inventories; Politicians; National Party